Kinerja Ekonomi Industri Informal Berbasis Pertanian di Kabupaten Bandung - Charina, Anne; Kusumo, Rani Andriani Budi; Mukti, Gema Wibawa (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
This study is motivated by the large number of informal agriculture-based industries in Bandung Regency that have survived for more than one generation. How their economic performance is interesting and important to study, amidst the many limitations and problems faced by the informal industry. A mixed method approach was used in this study. 115 informal agriculture-based industry units were selected as samples using the simple random sampling technique. Qualitative data were analyzed using the Thematic Analysis principle assisted by N-Vivo 12 software, while quantitative data processing for measuring economic performance used descriptive statistics. The results of the study show that the economic performance of the majority of informal agriculture-based industries (60%) has a Net Profit Margin of 5-19%, and 13% has an NPM >20% while 27% has an NPM <5%. The level of competition, innovation, market access and entrepreneur characteristics are factors that must be considered in improving economic performance in the informal industry.